Pengaruh Dosis Pupuk Kotoran Ayam dan Nitrogen terhadapPertumbuhan dan Hasil Sayur Sawi Daging (Brassica rapa L.) Varietas Gardena - DAVID HARYSUSANTO; GEDE WIJANA; NI LUH KARTINI (Fakultas Pertanian Universitas Udayana, 2014)
The Effects of Various Dose of Chicken Manure and Nitrogen Fertilizer on The Growth and Yield of Mustard (Brassica rapa L.) Var. Gardena. The Aim of the research was to find out optimal dose of chicken manure and nitrogen fertilizer and to find out those effects of both fertilizers and their interaction on the growth and yield of mustard. The research was carried out at Candikuning, Baturiti, Tabanan Regency, from April to June 2013. The experiment was factorial (two factors), with randomized block design (RBD). First factor was. chicken manure fertilizer dose, i.e. 0 ton ha-1, 15 ton ha-1 and 30 ton ha-1, while the second factor was nitrogen fertilizer with three levels of dose, i.e. 0 kg ha-1, 92 kg ha-1 and 184 kg ha-1. The result showed that there was no interaction effects of those two factors on all variables observed.. Dose of 15 ton ha-1 chicken manure and 92 kg/ha-1 nitrogen fertilizer resulted in highest yield and highest dry weight of shoots. However, the optimum dose (estimated with regression line) was150 kg ha-1 for nitrogen fertilizer and was 25,50 ton ha-1 for chicken manure.